2008
DOI: 10.1038/sj.bmt.1705972
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in long-term survivors of hematopoietic stem cell transplantation

Abstract: Our purpose was to determine the prevalence and features of metabolic syndrome (MS) in a series of long-term hematopoietic stem cell transplantation (HSCT) survivors. We assessed the clinical, metabolic and endocrinological data, and plasma TNF, leptin, resistin and adiponectin levels relating to 85 HSCT recipients. MS was diagnosed on the basis of the National Cholesterol Education Program-Adult Treatment Panel III criteria. Its prevalence was compared with that observed in an Italian population, and its rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
55
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 45 publications
(56 reference statements)
8
55
1
3
Order By: Relevance
“…A higher risk for transplanted patients was confirmed by several other studies. [9][10][11][12][13] Some authors have shown an increase in MS prevalence in patients who underwent TBI; 9 our previous study was consistent with this hypothesis. However, the mechanism that underlies the pathophysiology of MS after HSCT is still poorly understood; most studies in this field have heterogeneous or small cohorts, making it difficult to draw definitive conclusions about prevalence or risk factors of MS in transplanted patients.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A higher risk for transplanted patients was confirmed by several other studies. [9][10][11][12][13] Some authors have shown an increase in MS prevalence in patients who underwent TBI; 9 our previous study was consistent with this hypothesis. However, the mechanism that underlies the pathophysiology of MS after HSCT is still poorly understood; most studies in this field have heterogeneous or small cohorts, making it difficult to draw definitive conclusions about prevalence or risk factors of MS in transplanted patients.…”
Section: Introductionsupporting
confidence: 80%
“…However, the mechanism that underlies the pathophysiology of MS after HSCT is still poorly understood; most studies in this field have heterogeneous or small cohorts, making it difficult to draw definitive conclusions about prevalence or risk factors of MS in transplanted patients. 9,10,[12][13][14] In this study, we aimed to describe the prevalence and cumulative incidence over time of MS and its components in a relatively large prospective cohort of adults surviving childhood AL who received an HSCT and to define risk factors for this condition.…”
Section: Introductionmentioning
confidence: 99%
“…In long-term survivors of childhood cancer, the trends for increased risk of metabolic syndrome were observed in several studies (Talvensaari et al, 1996;Follin et al, 2006;Gurney et al, 2006;Oeffinger et al, 2006;Annaloro et al, 2008). As for survivors of adult-onset solid tumors, most studies were limited to some specific cancer types such as testicular cancer and prostate cancer (Nuver et al, 2005;Braga-Basaria et al, 2006;Haugnes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Частота метаболического синдрома и дислипиде-мии после алло-ТГСК у детей и взрослых достаточно высока и составляет 34-56 % [7]. По данным M. Taskinen et al [8], гипертриглицеридемия у детей после алло-ТГСК выявлена у 39 % пациентов, что существенно выше по сравнению с больными (8 %), получившими О р и г и н а л ь н ы е и с с л е д о в а н и я / О б з о р ы л и т е р а т у р ы только химиотерапию при лечении острого лимфо-бластного лейкоза (ОЛЛ).…”
unclassified
“…Метаболический синдром был диагностирован только у 3 (4 %) пациентов, что ниже, чем в других ра-ботах [7], и может быть объяснено меньшим возрастом реципиентов, наблюдавшихся в нашем исследовании.…”
unclassified